Non-CO2 Greenhouse Gas Mitigation Modeling with Marginal Abatement Cost Curves: Technical Change, Emission Scenarios and Policy Costs - Samuel Carrara; Giacomo Marangoni (Fondazione Eni Enrico Mattei (FEEM), 2013)
The abatement of non-CO2 greenhouse gases (OGHG) has proved to be of paramount importance for reaching global mitigation targets. The modeling of their abatement is normally carried out referring to marginal abatement cost (MAC) curves, which by now represent a standard approach for such an analysis. As no evolution scenarios are available to describe future mitigation opportunities for OGHGs, exogenous technical progress factors (TP) are normally imposed, producing progressive MAC dilatation over time. The main aim of this work is to perform a sensitivity analysis evaluating climate and economic effects of imposing various TPs under different policy scenarios: the analysis shows that TP variation has a considerable impact on the climatic and economic results.
Keywords: Q54; Q55; 330; Non-CO2 Greenhouse Gases; Marginal Abatement Cost Curve; Technical Change